2017
DOI: 10.1167/17.9.7
|View full text |Cite
|
Sign up to set email alerts
|

Feature singletons attract spatial attention independently of feature priming

Abstract: People perform better in visual search when the target feature repeats across trials (intertrial feature priming [IFP]). Here, we investigated whether repetition of a feature singleton's color modulates stimulus-driven shifts of spatial attention by presenting a probe stimulus immediately after each singleton display. The task alternated every two trials between a probe discrimination task and a singleton search task. We measured both stimulus-driven spatial attention (via the distance between the probe and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 68 publications
(108 reference statements)
2
10
0
Order By: Relevance
“…The priming effects of previewed features and location would be additive to maximize benefit in the same-colors experiment, and work in opposite directions to minimize cost in the swapped-colors experiment. Such spatial and feature-based preview effects would be independent, at least partly, and extend a recent finding that singletons attract spatial attention independently of feature priming (Yashar, White, Fang, & Carrasco, 2017) to include conditions of transsaccadic processing.…”
Section: Discussionsupporting
confidence: 82%
“…The priming effects of previewed features and location would be additive to maximize benefit in the same-colors experiment, and work in opposite directions to minimize cost in the swapped-colors experiment. Such spatial and feature-based preview effects would be independent, at least partly, and extend a recent finding that singletons attract spatial attention independently of feature priming (Yashar, White, Fang, & Carrasco, 2017) to include conditions of transsaccadic processing.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have reported no significant differences between upper versus lower locations along the intercardinal meridians, with intermediate performance relative to the VM and HM for stimuli presented at 45º within the four quadrants (e.g., Abrams et al, 2012;Cameron et al, 2002;Carrasco et al, 2004;Fuller & Carrasco, 2009). The fact that no significant difference emerges at 45º in most visual tasks has been used to justify collapsing performance across the four intercardinal isoeccentric locations (e.g., Barbot & Carrasco, 2017;Guzman-Martinez et al, 2011;Ling & Carrasco, 2006a, 2006bLiu & Mance, 2011;Montagna, Pestilli & Carrasco, 2009;Sawaki & Luck, 2013;Yashar et al, 2017). It is worth noting, however, that in the present study, a slight VMA asymmetry in SF sensitivity was still observed at 45º, which is consistent with the presence of a marginal asymmetry in contrast sensitivity at 45º (Abrams et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant information can come in several forms other than explicit current goals. For instance, information may be relevant based on the history of prior selections (e.g., Hickey et al, 2010 ; Awh et al, 2012 ; Yashar et al, 2017 ), permanent self-related goals such as one’s own name (e.g., Moray, 1959 ; Bargh, 1982 ), culture-related goals (e.g., Brosch and Sharma, 2005 ), or even phylogenetically implicit goals to perceive ecologically important stimuli such as potentially dangerous stimuli (e.g., Öhman et al, 2001 ; Flykt, 2005 ; New et al, 2007 ; Penkunas and Coss, 2013 ; Yorzinski et al, 2014 ) or salient, unique stimuli, as this study suggests.…”
Section: Discussionmentioning
confidence: 99%